EXPLORING THE INFLUENCE OF PERSONALITY TRAITS, RELIGIOSITY, AND LIFESTYLE ON THE FINANCIAL BEHAVIOR OF THE MILLENNIAL GENERATION - Erliana Djajanty Putri; Gunasti Hudiwinarsih; Rezza Arlinda Sarwendhi (Reviu Accounting, Business & Organizations, 2025)
Research Objective – This study aims to analyze the influence of personality attitude, religiosity, and lifestyle on the financial behavior of the millennial generation and to examine whether financial distress can moderate the relationship between personality attitude, religiosity, and lifestyle on the financial behavior of millennials. Method – The data analysis technique uses a structural equation model assisted by WrapPlS Version 7.0. The sample for this study consists of millennials in Kebomas District, Gresik Regency, with a convenience sampling technique amounting to 174 respondents. Findings – The results of this study show a significant influence of personality attitude on financial behavior and of religiosity on financial behavior. Financial distress can significantly moderate the influence of personality, religiosity, and lifestyle attitude on the financial behavior of the millennial generation, and there is no significant effect of lifestyle on the financial behavior of millennials. Theoretical and Policy Implications – The implications of this research can serve as a consideration for millennials in determining financial behavior in daily life. Research Novelty – The novelty of this study compared to previous research is the inclusion of financial distress as a moderating variable.